Mental Health Literacy Among Residents in Hien Chung Commune, Quan Hoa District, Thanh Hoa Province in 2022 - Dang Tuan, Mac; Thi Tinh, Le; Thi Kim Chi, Le; Thi Thu Hien, Le; Bach, Nguyen Xuan (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 39 No 3, 2023)
Objective: Describe the current state of mental health literacy of the community in Hien Chung commune, Quan Hoa district, Thanh Hoa province in 2022. Subjects and methods: In this cross-sectional study, a convenience sampling method was used to survey 198 participants in the commune. The data collection tools were the demographics section and the Vietnamese version of the Mental Health Literacy Scale (MHLS-VN). Results: The mean MHL total score of the sample was 79.1±13.9. Of these, the percentages of people having moderate mental health literacy and people having low mental health literacy were 66.1% and 18.2%, respectively. A small number of people with high mental health literacy accounted for 15.7%. Conclusion: People's mental health literacy is mainly low-medium.